A likely unavoidable clinical scenario during treatment for venous thromboembolism complicated with severe immune thrombocytopenia: A case report. Issue 9 (18th September 2021) - Takeuchi, Takaya; Matsuura, Yunosuke; Yamamura, Yoshimasa; Ohkusu, Momoko; Koyama, Shohei; Kawaguchi, Takeshi; Akaki Nagayasu, Mayumi; Komatsu, Hiroyuki; Okayama, Akihiko; Ishikawa, Tetsunori; Atsumi, Tatsuya; Kitamura, Kazuo
Abstract: Patients with immune thrombocytopenia have increased risks of bleeding and thrombosis. The acute‐phase treatment for venous thromboembolism complicated with severe immune thrombocytopenia involves a "platelet dilemma" in therapeutic decision‐making. Abstract : Patients with immune thrombocytopenia have increased risks of bleeding and thrombosis. The acute‐phase treatment for venous thromboembolism complicated with severe immune thrombocytopenia involves a "platelet dilemma" in therapeutic decision‐making.